Digital Financial Assets: Problems of Recognition, Valuation and Legal Regulation in Accounting - О. PYLYPENKO (National Academy of Statistics, Accounting and Audit, 2021)
The article reveals the author’s vision of the recognition, valuation and legal regulation of accounting of digital assets at company level.